Critical Roles of G3BP1 in Red-Spotted Grouper Nervous Necrosis Virus-Induced Stress Granule Formation and Viral Replication in Orange-Spotted Grouper (Epinephelus coioides) - Sun, Mengshi; Wu, Siting; Kang, Shaozhu; Liao, Jiaming; Zhang, Luhao; Xu, Zhuqing; Chen, Hong; Xu, Linting; Zhang, Xin; Qin, Qiwei; Wei, Jingguang (Frontiers in Immunology, 2022)
Viral infection causes changes in the internal environment of host cells, and a series of stress responses are generated to respond to these changes and help the cell survive. Stress granule (SG) formation is a type of cellular stress response that inhibits viral replication. However, the relationship between red-spotted grouper nervous necrosis virus (RGNNV) infection and SGs, and the roles of the SG marker protein RAS GTPase-activating protein (SH3 domain)-binding protein 1 (G3BP1) in viral infection remain unclear. In this study, RGNNV infection induced grouper spleen (GS) cells to produce SGs. The SGs particles co-located with the classic SG marker protein eIF3η, and some SGs depolymerized under treatment with the translation inhibitor, cyclohiximide (CHX). In addition, when the four kinases of the eukaryotic translation initiation factor 2α (eIF2α)-dependent pathway were inhibited, knockdown of HRI and GCN2 with small interfering RNAs and inhibition of PKR with 2-aminopurine had little effect on the formation of SGs, but the PERK inhibitor significantly inhibited the formation of SGs and decreased the phosphorylation of eIF2α. G3BP1 of Epinephelus coioides (named as EcG3BP1) encodes 495 amino acids with a predicted molecular weight of 54.12 kDa and 65.9% homology with humans. Overexpression of EcG3BP1 inhibited the replication of RGNNV in vitro by up-regulating the interferon and inflammatory response, whereas knockdown of EcG3BP1 promoted the replication of RGNNV. These results provide a better understanding of the relationship between SGs and viral infection in fish.